Strangers - Haddix, Margaret Peterson; Lambelet, Anne (New York, NY Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2020)
"What makes you 'you'? Chess has always been the protector of his younger siblings, Emma loves math, and Finn acts silly so he will be adored. They've been a happy family, the three of them and their mom. But everything changes when reports of three kidnapped children--who share the same first and middle names and exact birth dates--reach the Greystone family. This bizarre coincidence makes them wonder: Who exactly are these strangers? Before Chess, Emma, and Finn can ask their mom, she takes off on a mysterious work trip. Puzzling clues left behind lead to complex codes, hidden rooms, and a dangerous secret that will turn their world upside down."--Page 4 of cover
Includes excerpts from The deceivers and Remarkables.
Ages 8-12.
112896
Keywords: Missing persons -- Juvenile fiction; Siblings -- Juvenile fiction; Families -- Juvenile fiction; Secrecy -- Juvenile fiction; Brothers and sisters -- Fiction; Family life -- Fiction; Secrets -- Fiction; Supernatural -- Fiction; Juvenile works; Paranormal fiction; Fiction; Juvenile works; Paranormal fiction